Doświadczenie domu rodzinnego w narracjach (auto)biograficznych osób z rodzin polskich na emigracji - Teusz , Grażyna (Studia Edukacyjne, 2020)
The subject of the article is to present the experience and image of a family home that Polish family members have in exile. The direct area of reference presented on the basis of conducted (auto)biographical interviews is the German cultural and social context.